(untitled) (Bangladesh Journal of Animal Science, 2026)
This study was carried out to evaluate the sexual urge, semen quality, and non-return rate (NRR) of Black Bengal breeding bucks to establish criteria for selecting superior bucks. Data were collected from five bucks aged between 17 and 19 months over a period of five months. The results showed that, reaction time (RT) and erection status (ES) differed significantly among the bucks (p<0.05), whereas no significant (p>0.05) differences were observed for libido and fixing strength (FS). Moreover, significant difference (p<0.05) were also observed in semen volume and sperm concentration, whereas mass motility, progressive motility, live sperm, and normal sperm percentages were similar among the bucks. Furthermore, RT exhibited significant (p<0.05) strong negative correlations with both libido and FS, whereas ES showed significant (p<0.05) strong positive correlation with semen volume. In addition, strong and significant (p<0.05) positive correlations were observed among all key semen quality parameters. Finally, the bucks had an average NRR of 48.98 %, ranging from 33.33 % to 66.67 %. Buck 56 had the highest NRR and showed overall better performance in sexual urge, seminal parameters, fertility. These findings emphasize the importance of libido, semen quality, and NRR as reliable indicators for evaluating breeding soundness and improving reproductive efficiency in Black Bengal bucks. Bangladesh Journal of Animal Science 54 (4): 81-90, 2025